Optimizing log supply from timber concession complex, Dungun, Terengganu to their subsidiaries down stream processing mills using linear programming model / Ahmad Fauzi Puasa, Mohd Shahwahid Othman and Amir Abdul Nasir Shaari - Puasa, Ahmad Fauzi; Othman, Mohd Shahwahid; Shaari, Amir Abdul Nasir (2002)
This paper attempts to solve the problem of irregular supply of logs to the mills within the same holding company. Linear programming model analysis has been used in solving this problem. The logs supply from concession area is not sufficient. Buying additional logs from other log yards to meet the demand by the mills is recommended. The study shows that the supplier company can increase its net income by RM 1.5 million (before tax) if the log supply to the mills by buying logs buying from other concession areas is improved to an efficient manner.